Verify
(X+y)+z=
X=-11/12 y=-5/6 z=3
Answers
Answer:
5/3
Explanation:
(x + y) + z
(-11/12 + -5/6) + 3
((-11-5)/12) + 3
-4/3 + 3
(-4+9)/3
5/3
![](https://hi-static.z-dn.net/files/d75/3c17a39200de8517cc89d1fcbdfd1c32.jpg)
Correct Question : Verify (X + Y ) + Z = X + ( Y + Z)
Given : X = – 11 / 12 , Y = – 5 / 6 , Z = 3
LHS :
( X + Y ) + Z = [ ( – 11 / 12 ) + ( – 5 / 6 ) ] + 3
= [ ( – 11 – 10 ) / 12 ] + 3
= [ – 21 / 12 ] + 3
= ( – 21 + 36 ) / 12
= 15 / 12 – ( i )
RHS :
X + ( Y + Z) = – 11 / 12 + [ ( – 5 / 6 ) + 3 ]
= – 11 / 12 + [ ( – 5 + 18 ) / 6 ]
= – 11 / 12 + [ 13 / 6 ]
= ( – 11 + 26 ) / 12
= 15 / 12 – ( ii )
from ( i ) and ( ii)
LHS = RHS
Hence verified
Hope the solution is clear to you!!